Ecopharmacognosy: Exploring The Chemical And Biological Potential Of Nature For Human Health - Geoffrey A. Cordell (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
“Why didn’t they develop natural product drugs in a sustainable manner at the beginning of this century?” In 2035, when about 10.0 billion will inhabit Earth, will this be our legacy as the world contemplates the costs and availability of synthetic and gene-based products for primary health care? Acknowledging the recent history of the relationship between humankind and the Earth, it is essential that the health care issues being left for our descendants be considered in terms of resources. For most people in the world, there are two vast health care “gaps”, access to quality drugs and the development of drugs for major global and local diseases. Consequently for all of these people, plants, in their various forms, remain a primary source of health care. In the developed countries, natural products derived from plants assume a relatively minor role in health care, as prescription and over-the-counter products, even with the widespread use of phytotherapeutical preparations. Significantly, pharmaceutical companies have retrenched substantially in their disease areas of focus. These research areas do not include the prevalent diseases of the middle- and lower-income countries, and important diseases of the developed world, such as drug resistance. What then is the vision for natural product research to maintain the choices of drug discovery and pharmaceutical development for future generations? In this discussion some facets of how natural products must be involved globally, in a sustainable manner, for improving health care will be examined within the framework of the new term “ecopharmacognosy”, which invokes sustainability as the basis for research on biologically active natural products. Access to the biome, the acquisition, analysis and dissemination of plant knowledge, natural product structure diversification, biotechnology development, strategies for natural product drug discovery, and aspects of multitarget therapy and synergy research will be discussed. Options for the future will be presented which may be significant as countries decide how to develop approaches to relieve their own disease burden, and the needs of their population for improved access to medicinal agents.